Self‐navigation under non‐steady‐state conditions: Cardiac and respiratory self‐gating of inversion recovery snapshot FLASH acquisitions in mice. Issue 6 (7th January 2016) - Winter, Patrick; Kampf, Thomas; Helluy, Xavier; Gutjahr, Fabian T.; Meyer, Cord B.; Bauer, Wolfgang R.; Jakob, Peter M.; Herold, Volker
Abstract : Purpose: An algorithm is presented to enable cardiac and respiratory self‐gating in combination with Inversion Recovery Look‐Locker read‐outs. Methods: A radial inversion recovery snapshot FLASH sequence was adapted for retrospective cardiac T 1 measurements in mice. Cardiac and respiratory data were extracted from the k‐space center of radial projections and an adapted method for retrospective cardiac synchronization is introduced. Electrocardiogram (ECG) data was acquired concurrently for validation of the proposed self‐gating technique. T 1 maps generated by the proposed technique were compared with maps reconstructed with the ECG reference. Results: Respiratory gating and cardiac trigger points could be obtained for the whole time course of the relaxation dynamic and correlate very well to the ECG signal. T 1 maps reconstructed with the self‐gating technique are in very good agreement with maps reconstructed with the external reference. Conclusion: The proposed method extends "wireless" cardiac MRI to non‐steady‐state inversion recovery measurements. T 1 maps were generated with a quality comparable to ECG based reconstructions. As the method does not rely on an ECG trigger signal it provides easier animal handling. Magn Reson Med 76:1887–1894, 2016. © 2016 International Society for Magnetic Resonance in Medicine